2014
DOI: 10.4136/ambi-agua.1473
|View full text |Cite
|
Sign up to set email alerts
|

Tissue levels of the antioxidant enzymes superoxide dismutase and catalase in fish Astyanax bimaculatus from the Una River Basin

Abstract: This paper seeks to identify the biomarker response to oxidative stress in Astyanax bimaculatus, a freshwater fish, collected from the Una River and its associated water bodies. The fish were collected using fishing nets at three different points on the river basin, namely Fazenda Piloto (FP), Ipiranga (IP) and Remédios (RM), during the period from December 2013 to March 2014. Physical and chemical analyses of the water at the sample locations indicate that IP and RM possibly have larger concentration of eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 29 publications
0
12
0
4
Order By: Relevance
“…The present study showed that specimens from the P2 site had lower levels of renal SOD, while lower levels of this enzyme occurred in gills in fish from P3. Batista et al (2014) showed that the activity of hepatic SOD was higher in fish from P3, in comparison with that of P2. Therefore, SOD from liver, kidney or gills of A. bimaculatus could be used as a biomarker.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…The present study showed that specimens from the P2 site had lower levels of renal SOD, while lower levels of this enzyme occurred in gills in fish from P3. Batista et al (2014) showed that the activity of hepatic SOD was higher in fish from P3, in comparison with that of P2. Therefore, SOD from liver, kidney or gills of A. bimaculatus could be used as a biomarker.…”
Section: Resultsmentioning
confidence: 92%
“…These results indicate that only SOD was sensible to environmental conditions present in P2. The physicochemical analysis of the water of sites P1, P2 and P3 at the time of fish capture has already been published, as well as the map with the location of these sites (Batista et al, 2014, Ribeiro et al, 2015. These data from the physicochemical analyses indicated that: (1) the less impacted site was P1, although its total phosphate level (0.3 mg L -1 ) was slightly elevated in relation to reference values (0.1 mg L -1 ); (2) the conductivity of the P2 aquatic environment (198.7 S cm -1 ) was 1.9 times higher than in P1, and 1.6 times higher than in P3, showing that P2 fish were exposed to high levels of electrolytes from an impacted environment (CETESB, 2009); (3) P3 presented the highest values of chemical oxygen demand (COD), indicating abundance of organic matter in the water.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations